Dimerization and thiol sensitivity of the salicylic acid binding thimet oligopeptidases TOP1 and TOP2 define their functions in redox-sensitive cellular pathways - Westlake, Timothy J.; Ricci, William A.; Popescu, George V.; Popescu, Sorina C. (Frontiers in Plant Science, 2015)
A long-term goal in plant research is to understand how plants integrate signals from multiple environmental stressors. The importance of salicylic acid (SA) in plant response to biotic and abiotic stress is known, yet the molecular details of the SA-mediated pathways are insufficiently understood. Our recent work identified the peptidases TOP1 and TOP2 as critical components in plant response to pathogens and programmed cell death. In this study, we investigated the characteristics of TOPs related to the regulation of their enzymatic activity and function in oxidative stress response. We determined that TOP1 and TOP2 interact with themselves and each other and their ability to associate in dimers is influenced by SA. Biochemical characterization of the organellar TOP1 indicated sensitivity to redox changes and robust activity under a range of pH values. Treatments of top mutants with Methyl Viologen (MV) revealed TOP1 and TOP2 as a modulators of the plant tolerance to MV, and that exogenous SA alleviates the toxicity of MV in top background. Finally, we generated a TOP-centered computational model of a plant cell whose simulation outputs replicate experimental findings and predict novel functions of TOP1 and TOP2. Altogether, our work indicates that TOP1 and TOP2 mediate plant responses to oxidative stress through spatially separated pathways and positions proteolysis in a network for plant response to diverse stressors.